USING CLOGSTEREDU PRESENTATION IN WRITING SLAM POETRY COLLABORATIVELY IN ENGLISH CLASS - Faradiba Faradiba; Lina Satriyani (Universitas Negeri Padang, 2016)
Poetry can offer a wide range of language learning opportunities to EFL learners if it’s taught interactively and linguistically. Poetry is not only a tool for developing the written and oral skills of the students in the target language but also is a window opening into the culture of the target language that building up a cultural competence of the students. Slam poetry gives the students opportunity to write a poem independently. The process of organizing a slam also develops many soft skills. By stressing enjoyment, and presenting slam poetry through media of Glogster EDU and methods that provide maximum student involvement and interest, not only language learning can be facilitated, but learners at all levels can use the medium of poetry to express themselves in the target language. This paper describes the process that Senior High School EFL Learners went through in using Glogster EDU presentation in writing slam poetry collaboratively. By exploring the potentials and challenges, the result indicated that this study takes an interactive and collaborative approach through Glogster EDU and describes how poetry can be used to promote cooperation and communication as well as individual expression in the EFL class. In addition, the study also revealed challenges in the application of Glogster EDU which include the confusion in the implementation on the part of the students, and some technical problems.